2011
DOI: 10.1371/journal.pone.0016252
|View full text |Cite|
|
Sign up to set email alerts
|

Methylation at Global LINE-1 Repeats in Human Blood Are Affected by Gender but Not by Age or Natural Hormone Cycles

Abstract: Previously, we reported on inter-individual and gender specific variations of LINE-1 methylation in healthy individuals. In this study, we investigated whether this variability could be influenced by age or sex hormones in humans. To this end, we studied LINE-1 methylation in vivo in blood-derived DNA from individuals aged 18 to 64 years and from young healthy females at various hormone levels during the menstrual cycle. Our results show that no significant association with age was observed. However, the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
64
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 52 publications
20
64
2
Order By: Relevance
“…23 However, other authors have not found any association. 24 In our study, no relationship was found between both variables, but age was included as a possible confounder in all statistical analysis. Another risk factor related to global DNA methylation is gender.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…23 However, other authors have not found any association. 24 In our study, no relationship was found between both variables, but age was included as a possible confounder in all statistical analysis. Another risk factor related to global DNA methylation is gender.…”
Section: Discussionmentioning
confidence: 63%
“…It was observed, as in other studies that women had lower DNA methylation levels than men. 24 A few studies have investigated the association between physical activity and DNA methylation. Among them, Zhang et al reported a trend of higher levels of LINE-1 methylation with higher levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Genome-wide DNA methylation (e.g., measured in repetitive sequences including, Alu, Sat2, and LINE-1) in white blood cells (WBCs) has been shown to be associated with age, gender, race, alcohol exposure, and family history of breast cancer. [20][21][22][23][24] Additionally, compared to histologically normal or normal-appearing tissues (adjacent to breast tumors), tumor tissues consistently have lower levels of DNA methylation (i.e., increased hypomethylation throughout the genome), even early in breast carcinogenesis. 4,5,25 Furthermore, there are reports of significant associations between LINE-1 methylation and breast tumor clinicopathological features, 3 as well as breast cancer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although one study correlated lower levels of LINE-1 with increasing age, 36 most of the studies did not find an agedependent effect on blood LINE-1 methylation. 17,21,[37][38][39][40][41] In contrast, all of the studies investigating age and Alu methylation supported a lower level of DNA methylation of this repetitive element with increasing age. 34,36,37,41 Gene-specific methylation has been correlated with age in some studies ( Table 2).…”
mentioning
confidence: 82%
“…17,21,33,37,38,39,46 For example, total 5-mC content in WBC was higher in males than females in one study, 33 but this result was not replicated in a larger study measuring 5-mC. 18 Of the repetitive elements, LINE-1 has been investigated more frequently and was associated with lower levels in females compared to males in most 17,21,[37][38][39]46 but not all studies. 41 In contrast, there has been no consistent pattern associated with Alu methylation.…”
Section: Wbc Methylation and Diseasementioning
confidence: 96%